Predictors of increased costs following index adult cardiac operations: Insights from a statewide publicly reported registry. Issue 8 (3rd July 2019) - Aranda‐Michel, Edgar; Bianco, Valentino; Sultan, Ibrahim; Gleason, Thomas G; Navid, Forozan; Kilic, Arman
Abstract: Background: The aim of this study was to identify hospital‐level predictors of increased cost following index adult cardiac operations in a statewide registry. Methods: The Pennsylvania Health Care Cost Containment Council (PHC4) database was queried for isolated coronary artery bypass grafting (CABG), isolated valve surgery, or CABG plus valve surgery performed between 2014 and 2016. Charge‐to‐cost ratios for each individual hospital were used to estimate cost. Expected (predicted) operative mortality and 30‐day readmission were evaluated using multivariable risk models and linear regression analysis was utilized to evaluate the risk‐adjusted impact of multiple hospital‐level characteristics on costs. Results: During the study period, 29 578 patients underwent isolated CABG (n = 16, 641), isolated valve surgery (n = 8618), or CABG plus valve surgery (n = 4319) at 60 hospitals. The median cost of CABG was $61 573 (interquartile range [IQR] $50 780 to $77 482). The median cost of isolated valve surgery was $68, 835 (IQR $56 039 to $89 465) and CABG plus valve surgery $83 574 (IQR $69 806 to $114 407). Hospital‐level predictors of increasing costs in isolated CABG included higher predicted mortality rates, higher observed‐to‐expected (OE) mortality ratios, and nonteaching status. No hospital‐level independent predictors of increased costs were identified for isolated valve or CABG plus valve surgery. Conclusions: Hospitals that performed higher risk cases and had higher OE ratios for operative mortality in isolated CABG were found to have increased costs. These data collectively suggest that attention to risk assessment and outcome optimization efforts in isolated CABG would likely result in programmatic advantages not only from a clinical standpoint but also economic.